Review on thermal energy storage and eutectic nitrate salt melting point. Issue 1 (February 2021) - Samylingam, I; Kadirgama, K; Aslfattahi, Navid; Samylingam, L; Ramasamy, D; Harun, W S W; Samykano, M; Saidur, R
Abstract: In solar concentrates, thermal energy (TES) storage has a significant function (CSP). This article will discuss the forms of TES and TES content, focusing on the material for latent heat storage. Sensitive heat storage, latent heat storage and chemical reaction thermal storage classes can divide TES into three classes. Among the thermophysical properties for CSP is the latent heat storage content, which is used by more researchers. Dividing latent heat storage material into material for the organic, inorganic and eutetic phases change material (PCM). There are an advantage and downside to any form of storage material. Thermal stability at high temperature and low cost, however the specific heat capacity of the sensible heat storage material is very low compared to the latent heat storage materials..